Determinants of infertility among married women who attend gynecologic unit at health facilities of Gamo Zone and South Omo Zone, Southern Ethiopia: a case control study - Firehiwot Haile; Selamawit Gebeyehu; Hanan Abdulkadir; Yordanos Gizachew; Mesrach Hailu (Contraception and Reproductive Medicine)
Abstract Background Infertility defined as the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. Globally, infertility affects 15% of couples in the reproductive age. Purpose To identify determinants of infertility among married women who attend care at public health facilities of Gamo Zone and South Omo Zone, Southern Ethiopia. Patients and methods An Institution-based un-matched case–control study was conducted from May 1, 2022-May 30, 2023G.C. Participants were selected by systematic random sampling method after allocating the sample size proportionally to the health facilities. The data was collected by using the Open Data Kit (ODK) app through face-to-face interviews and exported to SPSS version 25 for analysis. The chi-square test and multivariable logistic regression model were used to identify determinants (P value < 0.05). Result A total of 760 married women (152 cases and 608 controls) in the reproductive age group were included in this study. The mean age of the respondents was 26.5(SD ± 5.27) years. In multivariable analysis: age, educational status of the woman, residence, family size, ever use of contraceptives, history of STI, history of abortion, menstrual pattern and current alcohol use were identified as determinants of infertility. Conclusion Factors such as older age, lower education, rural living, smaller families, lack of contraceptive use, history of STIs, past abortions, irregular periods, and current alcohol consumption were found to increase the risk of infertility. To reduce infertility rates, it is crucial to improve STI prevention, expand access to family planning services, and promote women's education.